2023
DOI: 10.3390/biomedicines11051252
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Shear Bond Strength and Degree of Conversion in Conventional and Self-Adhesive Systems Used in Orthodontic Bonding Procedures

Abstract: (1) Background: Self-adhesive systems have been proposed for the orthodontic bonding with the intention to reduce the traditional three-component system. (2) Methods: The sample consisted of 32 extracted intact permanent premolars randomly divided into two groups (n = 16). In Group I the metal brackets were bonded with Transbond XT Primer and Transbond XT Paste. In Group II the metal brackets were bonded with GC Ortho connect. The resin was polymerized for 20 s from two directions (mesial and occlusal) using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Higher filler content also limits the mobility of monomers and propagation of the polymerization reaction, resulting in a lower DC at the beginning [7,17], which consequently leads to a more extensive DC increase during the "dark" period [9]. Considering the large increase in DC values measured 1 day after polymerization for Enlight and Transbond XT in all groups, caution should be exercised when interpreting the results of other studies [6,8,10,[17][18][19]36] that measured the DC immediately after light curing. Generally, DC values measured within a period shorter than 1 day should be considered as gradually developing values, which are likely to vary depending on the time interval between the light curing and performing the measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Higher filler content also limits the mobility of monomers and propagation of the polymerization reaction, resulting in a lower DC at the beginning [7,17], which consequently leads to a more extensive DC increase during the "dark" period [9]. Considering the large increase in DC values measured 1 day after polymerization for Enlight and Transbond XT in all groups, caution should be exercised when interpreting the results of other studies [6,8,10,[17][18][19]36] that measured the DC immediately after light curing. Generally, DC values measured within a period shorter than 1 day should be considered as gradually developing values, which are likely to vary depending on the time interval between the light curing and performing the measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The increased bond strength observed in the laser-assisted bonding group aligns with previous research suggesting that laser irradiation can modify enamel surface characteristics, promoting improved adhesive interactions. [ 1 2 ] Knösel et al . [ 2 ] reported that laser treatment could enhance the micromechanical retention of brackets on enamel surfaces, thereby contributing to higher bond strength values.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 ] Knösel et al . [ 2 ] reported that laser treatment could enhance the micromechanical retention of brackets on enamel surfaces, thereby contributing to higher bond strength values. The microstructural alterations induced by lasers might lead to increased surface roughness and higher energy for adhesive interlocking, resulting in stronger adhesive bonding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SBS of the samples was measured by a universal testing machine (K-21046, Walter + bia, Iohningen, Switzerland). The force was applied by a beveled flat-end metal rod at the attachment‒composite resin interface with 1 mm/min crosshead speed, parallel to the bonding surface [ 21 ].…”
Section: Methodsmentioning
confidence: 99%